PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT PADA MATA PELAJARAN IPAS SISWA KELAS IV - Revalina Putri Nur'afni; Iqlimah Sobariyah; Hasna Apriliana; Maikel Kalolik; Teofilus Ardian Hopeman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to enhance the learning motivation of fourth-grade students in Science and Social Studies (IPAS) through the implementation of the Numbered Heads Together (NHT) cooperative learning model. The study was motivated by the issue of low student motivation, which negatively impacts learning outcomes. The Classroom Action Research (CAR) method was used, consisting of two cycles that included planning, implementation, observation, and reflection stages. The findings demonstrate that applying the NHT model effectively boosts students’ motivation, as reflected in increased participation, cooperation, and responsibility within groups. Based on these results, it can be concluded that the NHT cooperative learning model is effective in enhancing learning motivation in IPAS subjects for fourth-grade students.